Unsteady Turbulent Swirling Flows in a Thick Torus. Issue 13 (20th July 2023) - Sukhanovskii, Andrei; Batalov, Vladimir; Stepanov, Rodion; Frick, Peter
Abstract: Experimental study of unsteady swirling flows generated by special diverters in closed toroidal channels with different curvatures was carried out. The formation of a swirling flow in a toroidal channel is crucially different from the case of a straight cylindrical channel. It essentially depends on the curvature and is hindered by its increasing. The complex dynamics of swirling flow tightly connects with the interaction of jets after the diverter. Measurements of flow velocity using tracer's tracks showed that the evolution of the toroidal component in torus with one diverter can be divided into two-time intervals with different power laws. The evolution of the poloidal component is rather characterized by one slope "-2/3".